A comparison between a Coriolis meter and a combination method of a volumetric positive-displacement flowmeter and a densitometer in measuring liquid fuel mass flow at low flow rates. (December 2021) - Cheong, Kar-Hooi; Furuichi, Noriyuki; Doihara, Ryouji; Kamazawa, Shouta; Kasai, Shigenori; Hosobuchi, Nobuko
Abstract: This paper presents a comparative evaluation study of a newly developed mass flowmeter which combines a positive-displacement volumetric flowmeter and a densitometer, comparing its performance with a well-established Coriolis mass flow metering technology. The former which is a multiple-sensors measuring device shows a wider rangeability with a performance variation of within ± 1   % over the whole measuring range, whereas the latter which is a single-sensor measuring device shows an excellent performance in its optimum measuring range but exhibits larger performance variation up to about ± 25   % near the bottom limit of its measuring range.